(untitled) (Kerala Journal of Psychiatry, 2022)
This viewpoint article discusses the issues and difficulties that psychiatrists face when seeing patients with traumatic brain injury. Lack of proper instruments for assessment, lack of clarity on who is the medical authority for certification, confounding effects of comorbidities, etc. are discussed.